Die IgG4-assozierte Krankheit vom Standpunkt des Rheumatologen gesehen - Pipitone, N.; Vaglio, A.; Salvarani, C. (Aktuelle Rheumatologie, 2012)
The IgG4-related disease is a rare disorder with an estimated yearly incidence of 1 case per 100 000 population in Japan, characterized by the infiltration of IgG4-positive plasma cells into one or more organs. C-reactive protein and Serum IgG4 levels are often, but not invariably elevated. The most common clinical manifestation is lymphadenopathy, followed by autoimmune pancreatitis and sclerosing cholangitis. Imaging procedures are helpful to identify the affected organs and to monitor the disease course. However, biopsy is often required to secure the diagnosis. Glucocorticoids are the mainstay of therapy, but immunosuppressive agents are useful to prevent recurrences of disease in patients with a chronic relapsing course.
Keywords: IgG4; IgG4-related disease; chronic periaortitis; retroperitoneal fibrosis